2013
DOI: 10.1016/j.egypro.2013.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Quantification of Solar Radiation in Algeria

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Following a similar approach, the present study focuses on the regression analysis of these meteorological factors and extends to the non-linear impact of multivariate models which include variations of these parameters. Extensive studies were published to detail the non-linear analysis of GSR estimation models across various countries in the world [37][38][39][40][41][42].…”
Section: Mean Bias Error (Mbe) and Mean Absolute Bias Error (Mabe)mentioning
confidence: 99%
“…Following a similar approach, the present study focuses on the regression analysis of these meteorological factors and extends to the non-linear impact of multivariate models which include variations of these parameters. Extensive studies were published to detail the non-linear analysis of GSR estimation models across various countries in the world [37][38][39][40][41][42].…”
Section: Mean Bias Error (Mbe) and Mean Absolute Bias Error (Mabe)mentioning
confidence: 99%
“…The comparison with four other models (Angstrom-Prescott, Bahel, Newland and Abdala), reveals that the proposed model gives a better estimate with an MPE of 2.12%. Detailed examination of eight empirical models by Nia et al showed that the model combining sunshine duration, mean monthly temperature and mean relative humidity produces the lower RMSE of 1.91% [40]. This study has been conducted for the site of Algiers, Oran, Bechar and Tamanrasset.…”
Section: Semi-empirical and Parametric Modelsmentioning
confidence: 97%
“…The coldest month registers an average low temperature of 03 C at Bechar against 06 C at Algiers. 20 Relative humidity are higher in Algiers. Concerning the solar irradiance, Figure 12 shows obviously higher values for Bechar.…”
Section: Parametric Studymentioning
confidence: 97%